A review on the effectiveness of FRP and hybrid wrappings for strengthening concrete columns - Azzam Ahmed (Results in Engineering, 2025)
This review investigates the effectiveness of fibre-reinforced polymer (FRP) and hybrid wrappings in enhancing the axial compressive performance of concrete columns. It focuses on various FRP types, such as CFRP, GFRP, BFRP, and AFRP, as well as their configurations (full, partial, and hybrid). A systematic analysis covers mechanical performance, confinement efficiency, and recent advancements in analytical and finite element models. The review critically compares some selected design-oriented and analysis-oriented stress–strain models, categorizing them based on their applicability to fully and partially confined concrete. Emphasis is placed on low-strength concrete applications and novel hybrid systems. Unlike previous reviews, this study integrates recent experimental data, advanced modelling developments, and hybrid confinement systems into a unified framework, offering a comprehensive and practical resource for selecting and optimizing FRP confinement strategies, particularly for low-strength and partially confined concrete, thus addressing critical gaps in both research and design applications.